Efficacy and Safety of Letrozole in the Management of Constitutional Delay in Growth and Puberty: A Systematic Review and Meta-analysis - Deep Dutta; Rajiv Singla; Vineet Surana; Meha Sharma (Galenos Yayincilik, 2022)
No meta-analysis is available which has analysed the role of letrozole in constitutional delay in growth and puberty (CDGP). Electronic databases were searched for randomized controlled trials (RCTs) involving children with CDGP receiving letrozole. Primary outcomes were changes in predicted adult height (PAH) and pubertal progression. Secondary outcomes were alterations in bone age (BA), hormonal markers of puberty, bone mineral density and side-effects. One hundred-thirty articles were reviewed, from which seven RCTs which fulfilled all criteria were analysed. Letrozole was superior to placebo [mean difference (MD) 4.63 cm (95% confidence interval (CI): 3.90-5.36); p<0.01; I2=0%] but not testosterone [MD: 2.21 cm (95% CI: -1.71-6.16); p=0.27; I2=98%] with regards to improvement in PAH after 12-months use. Letrozole was superior to both placebo [MD: 4.80 mL (95% CI: 0.57-9.03); p=0.03] and testosterone [MD: 3.36 mL (95% CI: 0.58-6.75); p=0.02; I2=0%] with regards to improvement in testicular volume after 12-months use. Letrozole tended to be superior to testosterone [MD: -0.84 years (95% CI: 2.83-8.18); p=0.06; I2=0%] with regards to slowing in BA progression after 12-months use. Serum luteinizing hormone, follicle stimulating hormone, testosterone and inhibin-B were significantly higher after 6-months letrozole use compared to active as well as passive controls. No increased occurrence of adverse events, including spinal deformities, were noted with letrozole. Letrozole is safe and effective for improving height and pubertal outcomes in CDGP, and is better than testosterone with regards to improvement in testicular volume and may be better at delaying bone-age progression.